Tractors - McDonald, Amy (Minneapolis, MN : Bellwether Media, Inc., 2021)
"Developed by literacy experts in partnership with educators for students in PreK through grade two, this book introduces beginning readers to tractors through simple, predictable text and related photos"--
Includes bibliographical references and index.
Grades K-1.
108677
Keywords: Farm tractors -- Juvenile literature; Juvenile works; Readers